Evaluation Of The Antibacterial Properties Of The Methanol Root Extract Of Cnestisferruginea On Methicillin Resistant Staphylococcus Aureus (MRSA) (Journal of Pharmaceutical Negative Results, 2022)
AbstractThis study is aimed at investigating the antibacterial properties of the root bark extract against isolates of methicillin resistant Staphylococcus aureus (MRSA), and to identify the various phytochemicals responsible for this antimicrobial effects. The root barks of Cnestisferruginea were obtained, peeled, dried and extracted with the aid of a Soxhlet apparatus using 70% methanol, and then dried and concentrated. After which the aqueous and chloroform fractions were obtained by partitioning. MRSA samples were obtained from the Pharmaceutical Microbiology laboratory and confirmed using appropriate tests.The antibacterial efficacy of the Methanol extracts of dried root bark of Cnestisferruginea against isolates of MRSA, were determined using sensitivity test using different concentrations of the crude extract and the various fractions. The concentrations employed were 100mg/ml, 50mg/ml, 25mg/ml, 12.5mg/ml, and 6.25mg/ml. Higher concentrations of 300mg/ml, 150mg/ml, 75mg/ml, 37.5mg/ml, and 18.75mg/ml were also employed using the crude extract for further sensitivity test.Results obtained showed that the crude plant extract as well as the chloroform and aqueous fractions of the plant extract did not yield significant zones of inhibition indicating that the isolates were also resistant to the plant extract. Even at higher concentrations of the crude plant extract, similar results were seen. A further study was then also carried out with other test organisms comprising Staphylococcus aureus, Escherichia coli, and Proteus vulgaris, where significant zones of inhibition were seen at the different concentrations, confirming the antibacterial properties of the plant extract.This was done for the purpose of comparison and also to establish the true identity of the root extract of Cnestisferrugineaas an antibacterial agent and also to carry out further study on various other parts of the Cnestisferruginea plant with a view of discovering which plant part will effectively be able to effectively manage MRSA isolates.